Pengaruh Perubahan Posisi Dalam Mencegah Dekubitus Pada Pasien Tirah Baring Di Rsud Kabupaten Rejang Lebong Tahun 2025 - Lara Harnelia Sari; Tuti Rohani; Hengki Tranado (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Decubitus ulcers are system damage caused by prolonged pressure that often occurs in patients on prolonged bed rest. They can increase morbidity and delay healing. Preventive measures can be implemented through nursing interventions such as regular position changes. The purpose of this Research was to determine the effect of position changes on preventing decubitus ulcers in bed rest patients at Rejang Lebong District Hospital in 2025. This research used a quasi-experimental design with a one-group pre-test and post-test approach. The population was all 15 bed rest patients aged 60 years and older who were hospitalized for more than 3 days, using a total sampling technique. The research instrument used the Braden Scale to assess pressure ulcer risk. The intervention, which involved position changes every 2 hours during the day and every 5–6 hours at night for 3 days of treatment. Data were analyzed univariately and bivariately using paired t-tests. The results showed a difference in pressure ulcer risk scores before and after the position change intervention, with the average Braden score increasing after treatment. The statistical test obtained a p-value